2012
DOI: 10.1016/j.rpor.2011.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Sexual functioning of testicular cancer survivors and their partners – A review of literature

Abstract: With a growing number of TC survivors, a thorough investigation is required into their sexuality, both in an individual and dyadic dimension, so as to improve the quality of life of the affected young men, who take on their new social and professional roles in the period of highest reproductiveness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 18 publications
2
24
0
Order By: Relevance
“…Confirming previous research, we found that these sexual disruptions typically included erectile difficulties (Fergus et al, 2002), decreased desire (Mercadante et al, 2012), a de-prioritising of sex , sexual and bodily pain (Jensen et al, 2004) and increased body image concerns (Gilbert et al, 2010b(Gilbert et al, , 2011. The majority of existing research on changes in sexuality post-cancer has focused largely on cancers that directly affect the sexual or reproductive organs, such as prostate, testicular, breast and gynaecological cancer (Galbraith, Fink, & Wilkins, 2011;Gilbert et al, 2010bGilbert et al, , 2011Jankowska, 2012). However, our results show that disruptions to sexuality are not limited to cancers located in 'sexual' sites, with participants with leukaemia, multiple myeloma, colorectal cancer, brain cancer, as well as bowel, liver and lung cancer also reporting a range of disruptions to their sexuality.…”
Section: Discussionsupporting
confidence: 82%
“…Confirming previous research, we found that these sexual disruptions typically included erectile difficulties (Fergus et al, 2002), decreased desire (Mercadante et al, 2012), a de-prioritising of sex , sexual and bodily pain (Jensen et al, 2004) and increased body image concerns (Gilbert et al, 2010b(Gilbert et al, , 2011. The majority of existing research on changes in sexuality post-cancer has focused largely on cancers that directly affect the sexual or reproductive organs, such as prostate, testicular, breast and gynaecological cancer (Galbraith, Fink, & Wilkins, 2011;Gilbert et al, 2010bGilbert et al, , 2011Jankowska, 2012). However, our results show that disruptions to sexuality are not limited to cancers located in 'sexual' sites, with participants with leukaemia, multiple myeloma, colorectal cancer, brain cancer, as well as bowel, liver and lung cancer also reporting a range of disruptions to their sexuality.…”
Section: Discussionsupporting
confidence: 82%
“…), gynaecological (Stead et al . ), prostate and testicular cancers (Danile & Haddow ; Jankowska ). However, there is increasing evidence that both men and women across a range of cancer types report changes to their sexuality post cancer (Perz et al .…”
Section: Introductionmentioning
confidence: 99%
“…Previous research on cancer and sexuality has focused largely on cancers that directly affect the sexual or reproductive organs, such as prostate, testicular, breast and gynaecological cancer [11,12,34,35]. However, there is evidence that cancer also has an impact on the sexual wellbeing of people with non-reproductive cancers, such as lung and colorectal cancer e.g.…”
Section: Introductionmentioning
confidence: 99%